Smart-Devices in Human Behavior Manipulation: Process Diagram with Exploratory Assessment - Md. Mojibur Rahman Redoy Akanda; Md. Alamgir Hossain (International Journal of Engineering, Science and Information Technology, 2021)
Smart devices have become an essential part of human life with a bunch of modern features and facilities. Even in health care, health management, education, and the science sector use intelligent devices for their convenience. With the assertion of its wellness, people forget its downside and treating smart devices as their primary need. Whereas smart devices are tracking and collecting all user movements, including interest, boredom, and daily activity. As the data remain store in vendors' servers, and lightweight smart devices follow weak security, so data leakage also makes the data available to unauthorized parties. This sensitive data uses by vendors and  third-party for business and various purposes to influence and manipulate human behavior by showing content mapping to the collected data. Because of the huge involvement of the user in smart-device, marketing strategy also changed a lot. Digital marketing has been  introduced and become a key to success for many businesses where a particular content/advertisement can be mapped to particular leads. The next move of a user on the internet is shaping by applying numerous strategies based on previously collected data. In the era of smart devices, our personal life and personal data are not remaining personal anymore. This paper illustrates the systematic process of collecting and using data for manipulating human behavior. The raise of human behavior manipulation has been explained and an exploratory survey is imputed to strongly support the research statement.